Ecological Consequences of a Millennium of Introduced Dogs on Madagascar - Hixon, Sean W.; Douglass, Kristina G.; Godfrey, Laurie R.; Eccles, Laurie; Crowley, Brooke E.; Rakotozafy, Lucien Marie Aimé; Clark, Geoffrey; Haberle, Simon; Anderson, Atholl; Wright, Henry T.; Kennett, Douglas J. (Frontiers in Ecology and Evolution, 2021)
Introduced predators currently threaten endemic animals on Madagascar through predation, facilitation of human-led hunts, competition, and disease transmission, but the antiquity and past consequences of these introductions are poorly known. We use directly radiocarbon dated bones of introduced dogs (Canis familiaris) to test whether dogs could have aided human-led hunts of the island’s extinct megafauna. We compare carbon and nitrogen isotope data from the bone collagen of dogs and endemic ‘fosa’ (Cryptoprocta spp.) in central and southwestern Madagascar to test for competition between introduced and endemic predators. The distinct isotopic niches of dogs and fosa suggest that any past antagonistic relationship between these predators did not follow from predation or competition for shared prey. Radiocarbon dates confirm that dogs have been present on Madagascar for over a millennium and suggest that they at least briefly co-occurred with the island’s extinct megafauna, which included giant lemurs, elephant birds, and pygmy hippopotamuses. Today, dogs share a mutualism with pastoralists who also occasionally hunt endemic vertebrates, and similar behavior is reflected in deposits at several Malagasy paleontological sites that contain dog and livestock bones along with butchered bones of extinct megafauna and extant lemurs. Dogs on Madagascar have had a wide range of diets during the past millennium, but relatively high stable carbon isotope values suggest few individuals relied primarily on forest bushmeat. Our newly generated data suggest that dogs were part of a suite of animal introductions beginning over a millennium ago that coincided with widespread landscape transformation and megafaunal extinction.